THE ROLE OF MENTAL WORKLOAD, ORGANIZATIONAL COMMITMENT, COMPETENCE, KNOWLEDGE SHARING, AND WORK ENGAGEMENT ON CIVIL SERVANTS’ PERFORMANCE - Hidayat, Veny; Mulyana, Deddy; Sumin, Sumin; Setiawati, Farida Agus; Ayriza, Yulia (Faculty of Psychology, Universitas Diponegoro, 2023)
The combination of high job demands and low resources increases stress among employees, therefore organizations must ensure an appropriate workload. High job demands can be alleviated by maximizing job resources by recruiting competent, emotionally committed employees who are willing to share knowledge within the organization. This current study aims to examine the direct effects and the mediating role of work engagement on employee performance. The variables in this study were assessed through the utilization of adapted instruments, namely the Three Component Model (TCM) questionnaire for employee commitment, competencies adapted from occupational expertise and self-competence instruments, the UTRECHT Work Engagement Scale (UWES) questionnaire for work engagement, NASA TLX for mental workload, and Performance Instrument for employee performance. We conducted a cross-sectional study involving civil servants (ASN) in Tasikmalaya with a total of 243 respondents (Male = 51.4%, Female = 48.6%). Descriptive data analysis was conducted using Stata/MP 17.0, while hypothesis testing employed Structural Equation Modeling Partial Least Squares (SEMPLS). The findings indicate that most research hypotheses are accepted,particularly the influence of competence and commitment on work engagement, which validates previous research findings. Only commitment and mental workload do not have direct effects on performance. These findings serve as a reference for Human Resource Management (HRM) practitioners to develop human resources through training and development initiatives,thereby enhancing work engagement and subsequently improving employee performance productivity.